2013
DOI: 10.1186/1472-698x-13-8
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening health workforce capacity through work-based training

Abstract: BackgroundAlthough much attention has been given to increasing the number of health workers, less focus has been directed at developing models of training that address real-life workplace needs. Makerere University School of Public Health (MakSPH) with funding support from the Centers for Disease Control and Prevention (CDC) developed an eight-month modular, in-service work-based training program aimed at strengthening the capacity for monitoring and evaluation (M&E) and continuous quality improvement (CQI) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 15 publications
3
48
0
4
Order By: Relevance
“…Most programs took place in the southern African region [10, 12, 13, 20], followed by Uganda [16, 18]. Malawi [21], Nigeria [14], Cameroon [17], and the Democratic Republic of Congo [19] were also represented.…”
Section: Resultsmentioning
confidence: 99%
“…Most programs took place in the southern African region [10, 12, 13, 20], followed by Uganda [16, 18]. Malawi [21], Nigeria [14], Cameroon [17], and the Democratic Republic of Congo [19] were also represented.…”
Section: Resultsmentioning
confidence: 99%
“…However, the key gaps have been on sustainability issues over time. Work-based capacity-building approaches in the long term are expected to promote retention of health workers as well as improve service delivery [14]. Work-based training approaches have been implemented to strengthen professional capacity [15] and to increase health workers’ capacity to improve maternal, newborn and child health-service delivery.…”
Section: Introductionmentioning
confidence: 99%
“…These professionals were, however, often found lacking in critical leadership knowledge and skills. [2][3][4] Because of this deficiency, health workers may fail to deliver quality healthcare services, resulting in patients resorting to unsafe methods of treatment. Poor leadership and management skills have led to mishandling of resources, which has also impacted on the health sector.…”
Section: Researchmentioning
confidence: 99%
“…Strategies that have been put in place to improve health system challenges included leadership training among healthcare workers in Uganda. [9] In a modular work-based training model Matovu et al [2] found that having a programme model that combined both educational and work-based training was very effective in strengthening the capacity and competency of Ugandan health workers. [1] MUST's approach was unique in that they saw the importance of using the LDP for undergraduate students before these students practised in the community.…”
Section: Researchmentioning
confidence: 99%